Vegetation and pollen along a 200-km transect in Khyber Pakhtunkhwa Province, northwestern Pakistan. (1st September 2016) - Jan, Farooq; Schüler, Lisa; Behling, Hermann
Abstract : This paper presents the first study on the relationship between vegetation and modern pollen rain along a 200-km elevational gradient (275–2600 m above sea level), in the Khyber Pakhtunkhwa Province of northwestern Pakistan. A vegetation survey of 24 plots (six plots of 10 × 10 m from four elevational zones) was carried out following the Braun-Blanquet method. The percentage cover of all taxa was documented and species were assigned to their respective families. Twenty-four surface samples (taken from the same plots from which the vegetation data were recorded), were processed according to standard methods for retrieving pollen grains. Based on a count of 300 pollen grains per sample, the percentage abundance of taxa in the pollen assemblages was compared to the corresponding percentage of cover abundance in the vegetation, at the family level. Results of the constrained incremental sum of squares (CONISS) derived from the pollen data reveal that the natural vegetation zonation is well reflected in pollen assemblages despite alteration of the vegetation by human activities. The identification of key taxa for the different vegetation zones improves our confidence to draw vegetation boundaries and distinguish the elevational zones along the gradient. The Spearman's rank correlation coefficient at P < 0.05 indicates a significant correlation between vegetation cover and pollen rain in Acanthaceae, Asteraceae, Cyperaceae, Euphorbiaceae, Poaceae, and Verbenaceae, whereas weak correlations were observed in Apiaceae, Balsaminaceae, Boraginaceae, Rubiaceae, and Saxifragaceae. Results based on the comparison of vegetation and the pollen spectra at the family level, and their transfer factors (TF), reveal that large-sized Asteraceae, Brassicaceae, Cannabaceae, Chenopodiaceae/Amaranthaceae, Myrtaceae, Poaceae/cereal pollen grains > 45 µm, and Polygonaceae reflect the proximity of cultivated land and human habitation in the lower three vegetation zones of Peshawar valley, lower montane Malakand hills and Swat valley. Contrarily, the abundance of the Dryopteridaceae, Pinaceae, Pteridaceae and certain spores reflects natural vegetation in the upper montane Malam Jabba zone.